Komparasi kinerja perusahaan pariwisata, restoran dan hotel sebelum dan selama pandemi covid-19 - Dwi Dewisri Kinasih (Jurnal Kajian Manajemen dan Wirausaha, 2022)
This study aims to determine the performance of tourism companies, restaurants and hotels during and before the covid 19 pandemic. This study uses four proxies to measure company performance, namely ROA, ROE, Tobins Q and NPM. The data analysis technique used is to perform a different test before the pandemic and during the covid 19 pandemic. The sampling technique used is a purposive sampling technique based on certain criteria. The number of samples in this study were 15 companies with 120 observations. This study shows that there are differences in the performance of tourism, restaurant and hotel companies before the pandemic and during the pandemic as measured by ROA, ROE and NPM. However, there is no difference in company performance as measured by Tobins Q.